Insight on the complete process of photoacoustic generation and propagation of cerebrovascular in brain via multi-physics coupling method - Shangkun Hou; Anzhi Lv; Jiabin Lin; Bokang You; Shuaixin Huang; Xianlin Song (AIP Advances)
The presence of the skull hinders photoacoustic imaging from being used for brain imaging. In order to understand the mechanism of photoacoustic signal generation of cerebrovascular in the presence of skull, a photoacoustic model of cerebrovascular was established by using COMSOL Multiphysics to achieve the visualization of the whole process of the generation and transmission of the cerebrovascular photoacoustic signal. The diffusion equation is approximated by the partial differential equations in the form of coefficients in the mathematical module of COMSOL to describe laser propagation in brain tissue. The light energy absorbed by the gray matter and blood vessels was used as a heat source, and the biological heat transfer module of COMSOL Multiphysics was used to describe the instantaneous temperature rise of gray matter and blood vessels. A thermal strain model was constructed by the solid mechanics module to visualize the surface displacement caused by the adiabatic expansion of blood vessels. The photoacoustic signal is generated by the surface displacement of the vessel, and the propagation of the photoacoustic signal is visualized using a transient pressure acoustic model of COMSOL Multiphysics. This visualization study provides theoretical guidance for the research and application of photoacoustic imaging in brain structural and functional imaging.